2016
DOI: 10.2298/csis150122044u
|View full text |Cite
|
Sign up to set email alerts
|

S-TFRC: An efficient rate control scheme for multimedia handovers

Abstract: The integration of heterogeneous wireless access technologies has numerous issues for multimedia applications, such as to smoothly continue over new connections without any service disruption during vertical handovers. We propose State-Aware Feedback extension to Datagram Congestion Control Protocol (DCCP) that meets QoS requirements of multimedia applications throughout the handover process. We consider movement of mobile subscribers among heterogeneous access technologies from highly unstab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…SR-DMM focuses on providing L3 improvements such as L3 handover latency reduction. However, there are other solutions, which include improvements at the link-layer [21,22], but they are out of the scope of this paper.…”
Section: Sr-dmm Solutionmentioning
confidence: 99%
“…SR-DMM focuses on providing L3 improvements such as L3 handover latency reduction. However, there are other solutions, which include improvements at the link-layer [21,22], but they are out of the scope of this paper.…”
Section: Sr-dmm Solutionmentioning
confidence: 99%
“…In [19], the authors analyzed the performance of TFRC to transport multimedia applications over homogeneous wired networks and found that TFRC needs improvement in homogeneous wired networks. To increase the ability of TFRC, authors proposed State-TFRC (S-TFRC), which includes a feedback mechanism which exchanges link information and transmission parameters.…”
Section: Literature Surveymentioning
confidence: 99%
“…Several systems in the network environment monitor for impending congestion before it occurs. The QoS design is a fundamental feature of nextgeneration IP routers to enable differentiated delivery and to ensure delivery quality for various service traffic [5], [20], [27]. Although the TCP protocol handles "dataoriented applications" firmly, so UDP protocol mostly being utilized for the streaming relevance.…”
Section: Introductionmentioning
confidence: 99%